Perubahan Nilai Desorpsi Produk Kakao Fermentasi Pada Berbagai Suhu dan Kelembaban - Sri Widata (Department Industrial Engineering, University of Muhammadiyah Malang, 2010)
Cocoa is product of can to experience desorptions process, when moisture content more than equillibrium moisture content. This of moisture desorptions process, as usually to result in unbelievable activity of microorganism. That is often can to drop of product quality. Desorptions process necessary to study and to know so that if to preserve, cocoa fixed of high quality. The obyectives of this research is known bigness of desorptions value is happen at cocoa fermented of product. The result of research was shown that 77,8% sample, to experience desorptions prosess. This to happen at temperature 20ºC, 30ºC and 50ºC. Highest of desorptions value is 0,1473 and to happen at temperature 50ºC with humidity 11%. Just low of desorptions value is 0,0133 and to happen at temperature 20ºC With humidity 54%. The result of research also shown that increase of temperature cause to heighten of desorptions process. Just with increase of humidity cause to decrease of desorptions process.